2021
DOI: 10.1021/acsaem.1c01839
|View full text |Cite
|
Sign up to set email alerts
|

Surface De-Fluorination and Bond Modification of CFx by High-Density Hydrogen Plasma Processing

Abstract: The Li/CF x (lithium/fluorinated carbon) primary battery has attracted worldwide interest from the academic community and industry. However, Li/CF x batteries encounter the issue of poor rate capability because of the poor electronic conductivity of CF x due to the strong covalent C–F bond. Herein, we reported a vapor-phase method, namely, a low-temperature plasma technique, to modify the surface morphology, chemical components, and the microstructure of CF x . High-density hydrogen plasma processing partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Energy & Environmental Science Review discharge current of 4 C. 178 Etching increased the amount of surface C, which increased the conductivity of the CF x material.…”
Section: Modification Of Cf X Materialsmentioning
confidence: 99%
“…Energy & Environmental Science Review discharge current of 4 C. 178 Etching increased the amount of surface C, which increased the conductivity of the CF x material.…”
Section: Modification Of Cf X Materialsmentioning
confidence: 99%
“…By controlling the temperature, the fluorinated graphitized CNTs were optimized to an exact ratio, which exhibited high specific capacities of 798.8 mAh g –1 , nearly reaching the theoretical value in that F/C ratio . This strategy is the most frequently used method to improve performance of the CF x /Li cell, which has been widely applied by a series of works. ,, It should be noted that surface defluorination can improve the conductivity on the surface of CF x , making the interfacial C–F bond become more ionic than covalent, to acquire better rate performance . During surface defluorination, inactive -CF 2 and -CF 3 was removed and enabled CF x a more conductive surface .…”
Section: Cf X As Cathode Materials For Primary Batteriesmentioning
confidence: 99%
“…44,45,47−49 It should be noted that surface defluorination can improve the conductivity on the surface of CF x , making the interfacial C−F bond become more ionic than covalent, to acquire better rate performance. 50 During surface defluorination, inactive -CF 2 and -CF 3 was removed and enabled CF x a more conductive surface. 51 However, the direct F 2 method requires equipment of high safety, for F 2 is very dangerous.…”
Section: Cf X As Cathode Materials For Primary Batteriesmentioning
confidence: 99%
“…24 However, the working conversion reaction of CF x as well as the generation and chemical stability of semi-ionic bonds are not well-understood to harvest the full potential of these materials in realizing sustainable energy densities for longer operations. 25,26 To achieve high-performance CF x materials certain materials characteristics need to be tuned in such a way that the resulting materials exhibit higher conductivity, larger semi-ionic bonds, and easy diffusion of lithium ions. 27,28 It has been observed that semi-ionic bonds play a crucial role in pushing the performance by providing better conductivity, discharge voltage and rate capability, 7,19,22,29 while the covalent bonds are chemically more stable with higher bond energies which reduced the performance.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 To achieve high-performance CF x materials certain materials characteristics need to be tuned in such a way that the resulting materials exhibit higher conductivity, larger semi-ionic bonds, and easy diffusion of lithium ions. 27,28 It has been observed that semi-ionic bonds play a crucial role in pushing the performance by providing better conductivity, discharge voltage and rate capability, 7,19,22,29 while the covalent bonds are chemically more stable with higher bond energies which reduced the performance. 30 Therefore, it is highly important that the CF x materials should contain more semi-ionic bonds than covalent ones to ensure high performance.…”
Section: Introductionmentioning
confidence: 99%